1993
DOI: 10.1177/074355489382005
|View full text |Cite
|
Sign up to set email alerts
|

Family Differentiation, Peer Differentiation, and Adolescent Adjustment in a Clinical Sample

Abstract: This is a study of the relationships among family system dynamics, peer network characteristics and adolescent personal adjustment. Specific characteristics of both the family system and the peer network are thought to have a significant impact on the adolescent's ability to master certain developmental tasks and therefore contribute to the adolescent's ongoing growth and development. Apart from the separate influences of these factors, the study attempts to explore the combined influence offamily system and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…This is consistent with the family systems literature which shows that successful promotion of intimacy is associated with minimized conflict and the communication lower instances of FI (Bartle-Haring & Gavazzi, 1996;Gavazzi, 1993Gavazzi, , 1994. Thus, the present study supports the belief that when familial social support is adequate the individual's need for support, information, and feedback are fulfilled by maintaining boundaries that restrict intrusive interactions (Caplan, 1974;Procidano, 1978Procidano, & 1983.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with the family systems literature which shows that successful promotion of intimacy is associated with minimized conflict and the communication lower instances of FI (Bartle-Haring & Gavazzi, 1996;Gavazzi, 1993Gavazzi, , 1994. Thus, the present study supports the belief that when familial social support is adequate the individual's need for support, information, and feedback are fulfilled by maintaining boundaries that restrict intrusive interactions (Caplan, 1974;Procidano, 1978Procidano, & 1983.…”
Section: Methodssupporting
confidence: 88%
“…The Family Intrusiveness Scale (FIS) is a 13-item questionnaire that assesses family communication in terms of distance regulation and system tolerance for individuality (Gavazzi, Anderson & Sabatelli, 1993). Each response is placed upon a five-point Likert Scale where 1 represents "Never" and 5 indicates "Always."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews of research grounded in family systems theory (Charles 2001;Miller et al 2004) confirm that support exists for theoretically posited relations between differentiation of self and greater psychological well-being (e.g., Elieson and Rubin 2001;Gavazzi et al 1993;Skowron and Schmitt 2003;Tuason and Friedlander 2000), lower chronic anxiety (Skowron and Friedlander 1998), greater relationship satisfaction (Skowron 2000), fewer interpersonal problems (Wei et al 2005), and lower relationship violence (Rosen et al 2001;Skowron and Platt 2005). However, unlike previous studies that have relied on use of cross-sectional designs, we employed a longitudinal design in the current study in order to test the Bowen family systems theory assertion that differentiation of self leads to greater psychological well-being and interpersonal competence.…”
Section: Introductionmentioning
confidence: 89%
“…Adolescent research on relationships, including friendships, has also found significant associations between adjustment and intimacy. The higher levels of social support and lower levels of peer pressure resulting from intimate relationships (including peer networks/ friendships) were associated with better overall adolescent adjustment, and they were better predictors of adolescent psychological adjustment than measures of popularity (Gavazzi, Anderson, & Sabatelli, 1993;Townsend, McCraken, & Wilson, 1988). Research into the relations between the nature of friendships, including attachment, intimacy, and conflict, and several aspects of adjustment, including impulse control, emotional tone, mastery of the external world, and psychopathology has found that the two friendship variables that accounted for significant variance in psychopathology scale scores were attachment and conflict (Claes, 1992).…”
Section: Intimacy Vs Isolationmentioning
confidence: 98%